Circ_0091702 relieves lipopolysaccharide (LPS)-induced cell injury by regulating the miR-182/PDE7A axis in sepsis. Issue 9 (2nd June 2021) - Zhang, Xinliang; Dong, Shimin
ABSTRACT: Circular RNA plays an important role in the progression of sepsis. Circ_0091702 has been found to be an important regulator of sepsis progression, so its role and mechanism in sepsis progression deserve to be further explored. Lipopolysaccharide (LPS) could suppress cell viability, while enhance cell apoptosis and inflammation to induce cell injury. Circ_0091702 was downregulated in LPS-induced HK2 cells, and its overexpression alleviated LPS-induced cell injury. MiR-182 could be sponged by circ_0091702. Moreover, miR-182 inhibitor could relieve LPS-induced cell injury, and its overexpression also reversed the inhibition of circ_0091702 on LPS-induced cell injury. PDE7A was a target of miR-182, and its expression was reduced in LPS-induced HK2 cells. Additionally, silencing of PDE7A reversed the suppressive effect of circ_0091702 on LPS-induced cell injury. Our data suggested that circ_0091702 sponged miR-182 to regulate PDE7A, thereby alleviating LPS-induced cell injury in sepsis. Graphical Abstract: